A Comparison of Anterior and Posterior Dental Autotransplants: A Systematic Review - Galletti, Fulvia; Motta Jones, Niccolò; Real-Voltas, Francisco; Greethurst, Alice Rose; Stagno d'Alcontres, Lorenza; Cervino, Gabriele; Fiorillo, Luca; De Angelis, Francesca; Galletti, Cosimo (European Journal of General Dentistry, 2024)
The ability to restore both function and aesthetics after tooth loss is a cornerstone of modern dentistry. Various treatments are available for replacing missing teeth, among which dental autotransplantation has emerged as an innovative approach. Historically, tooth autotransplantation has been a common remedy for dental avulsion in young patients; however, in recent years, it has gained recognition as a viable and predictable option for replacing hopeless teeth in adults as well. This study aims to systematically evaluate and compare the effectiveness of anterior versus posterior dental autotransplants, while also providing an overview of the techniques employed in these procedures. Utilizing online platforms such as PubMed and the UIC University library, articles published between 2010 and 2023 were selected for review. The findings of this systematic review indicate that dental autotransplantion, regardless of whether it occurs in the anterior or posterior region, yields optimal aesthetic and functional results alongside long-term positive outcomes. Autotransplantation is particularly beneficial for trauma-related tooth loss, especially in younger patients, where ongoing bone growth necessitates the preservation of bone levels. The studies reviewed consistently demonstrate that this technique offers significant advantages in terms of function, appearance, and structural integrity, with compelling evidence supporting its long-term viability. In summary, dental autotransplantation is a valuable treatment option that not only addresses the immediate concerns following tooth loss but also contributes to maintaining oral health and aesthetics over time.
Keywords: dental autotransplants; dental autotransplantation; anterior sector; posterior sector; success rate